Study of Prevalence of Neonatal Septicaemia and Detection of Antibiotic Resistance in Besat Hospital in Iran - N Bahmani (Tehran University of Medical Sciences, 2007)
Background: Septicemia is one of the most important neonatal diseases which occurrs as a result of bacterial infection. The major criterion for its diagnosis is based on body fluid cultures specially blood culture. The aim of this study is to determine the prevalence of septicemia and also detection of isolated bacterial sensitivity to selected antibiotics in neonatal ward of Besat Hospital. Methods: This study is descriptive. Blood cultures were ordered for all hospitalized neonates. A questionnaire including clinical manifestations of septicemia such as fever, hyporeflexia, hypothermia, cyanosis, abdominal distention, loss of appetite and jaundice was filled out for every neonate clinically suspected of having septicemia. At last the collected data were analyzed by means of SPSS software and descriptive statistics. Results: This study included 700 specimen of blood cultures, 17.6% of the cases were suspected of having septicemia but %30 of them had positive blood cultures. The most common species isolated was coagulase negative staphylococci. As to sign and symptoms hyporeflexia, juandice, and anorexia were detected most frequently. Sensitivity of gram negative bacteria to ciprofloxacin was 100% & to cefotaxime 66.7%. Sensitivity of gram positive bacteria to cephalotin was 43%, while gram negative bacteria had highest resistance rate to ampicilin & cephalotine in 100% and gram positive bacteria to oxacilin in 68.6% & cotrimoxasol in 62.9% of the cases. In this study prevalence of septicemia in those having positive blood cultures was 30% with a mortality rate of 4.9%. Conclusion: This research shows that clinical manifestation is not enough for the diagnosis of septicemia and blood cultures should be considered necessary in suspected cases. Considering high resistance rate of isolated bacteria to ampicilin & cephalotin, culture and antibiogram can be of great value to select suitable antibiotic. Ciprofloxacin can be regarded as the drug of choice for gram negative bacteria. To reduce prevalence and mortality rates of septicemia, proper planning to confront microorganisms & nosocomial infections is necessary. Also appropriate and timely prescription of antibiotics by pediatricians can prevent bacterial resistance to antibiotics.